Disparities in anxiety and related factors among Chinese older adults across different aged-care models: a comparison of two cross-sectional studies - Xin Zheng; Ziwen Xu; Jiajie Zhao; Sanyuan Hao; Fuqin Xu; Shuo Ding; Guoqing Liu; Shufan Yang; Benjamin Otsen; Wen Zhu; Zhongliang Bai; Jie Yang; et al. (BMC Geriatrics)
Abstract Background Anxiety disorders in older adults have become a prominent public health problem due to their concomitant chronic conditions, reduced quality of life and even death. However, fewer studies have been conducted on differences in anxiety among older individuals in different aged-care models, and the interactive relationship between the influencing factors on anxiety remains unclear. The study aimed to examine the disparities in the prevalence of anxiety between community-dwelling and institutionalized older adults and related influencing factors. Methods Data were collected from the Anhui Healthy Longevity Survey (AHLS) and the Anhui Elderly Caring Social Organizations Survey (AECSOS). Data on demographic variables, lifestyle factors and health-related variables in 6968 older adults were used for analysis. Anxiety symptoms were evaluated using the Generalized Anxiety Disorder Assessment Scale (GAD-7). Binary logistic regression models and a Classification and Regression Tree model (CART) were utilized to examine the relationship between variables. Results The prevalence of anxiety were 24.3% and 16.7% among community-dwelling older adults and institutionalized older adults, respectively. Several factors including age, gender, residence, education, income level, live alone, and number of chronic diseases showed a linkage with anxiety among community-dwelling older adults. For the institutionalized older adults, gender, residence, source of income, and number of chronic diseases exhibited a significant association with anxiety. We noted the interactive effect, suggesting that community-dwelling female older adults with an income level of less than 6500 RMB per year and reported chronic disease comorbidities had the highest likelihood of anxiety, and institutionalized female older adults with income sources such as pension, subsidy, family providing, and resident in rural areas have the greatest risk of experiencing anxiety. Conclusions This study has brought to light the higher risk of anxiety among community-dwelling older adults compared to institutionalized older adults. Targeted interventions are, therefore emphasized to address the negative impact of anxiety for populations at higher risk.